Visible-light driven CO2 reduction coupled with water oxidation on Cl-doped Cu2O nanorods. (June 2019) - Yu, Luo; Ba, Xin; Qiu, Ming; Li, Yifei; Shuai, Ling; Zhang, Wei; Ren, Zhifeng; Yu, Ying
Abstract: Visible-light driven overall conversion of CO2 and H2 O into chemical fuels and O2 is a challenging but promising reaction for artificial photosynthesis. Here we demonstrate Cl-doped Cu2 O nanorods for photocatalytic CO2 reduction conjugated with H2 O oxidation under visible-light irradiation. Cl-doping optimizes the band structure of Cu2 O, resulting in a more positive valence-band position for H2 O oxidation, and promotes CO2 adsorption capacity as well as separation and transfer efficiency of photogenerated charge carriers. Consequently, the Cl-doped Cu2 O shows excellent photocatalytic CO2 reduction performance accompanied by favorable H2 O oxidation ability under visible-light irradiation. The best sample achieves an apparent quantum efficiency of 2.2% with 1.13% for CO and 1.07% for CH4 at 400 nm and demonstrates superior stability. Density functional theory calculations further reveal that Cl-doped Cu2 O is beneficial for the transformation of CO2 into the intermediates of *COOH, *CO, and *CH3 O, which contributes to the enhanced activity of CO and CH4 production. Additionally, Cl-doped Cu2 O shows stronger affinity toward the *CO intermediate, which tends to be protonated and ultimately transforms into CH4, leading to higher selectivity of CH4 than that of pure Cu2 O. This work validates an effective strategy to engineer Cu2 O for visible-light driven overall conversion of CO2 reduction and H2 O oxidation. Graphical abstract: Image 1 Highlights: Cl-doped Cu2 O nanorods are synthesized via a facile electrodeposition method. Cl-doping optimizes the band structure of Cu2 O, resulting in a more positive valence-band position for H2 O oxidation. The Cl-doped Cu2 O acts as an efficient catalyst for CO2 reduction and H2 O oxidation under visible-light irradiation. The best sample achieves an apparent quantum efficiency of 2.2% with 1.13% for CO and 1.07% for CH4 at 400 nm.